Sifat Dasar dan Kegunaan Kayu Agathis (Agathis hamii M. Dr.) dari Sulawesi Selatan (Jurnal Penelitian Kehutanan Wallacea, 2017)
Wood proper uses of tree species can be determined by it’s basic properties. This research was carried out to examine the basic properties (anatomical structure, chemical, physical and mechanical) of agathis (Agathis hamii M. Dr.) wood from natural forest in Sulawesi. Proper uses of wood was determined by considering their basic properties and uses which the local community have currently employed. Results revealed that agathis heartwood is whitenish to yellow brownish colour; fine texture; straigh grain; glossy; rather soft; moderate in specific gravity; moderate in dimensional shrinkage; strenght class III; high in cellulose and pentose content; low in lignin, extractive and ash content; remarkably long fiber and thin wall thickness; fiber grade is very good for pulp/paper manufacture. Appropirate uses of agathis are for light construction material in house building and certain ship components, furniture, handicraft and wood industry.
Keywords: Wood basic properties; Agathis hamii; Wood uses